Acceleration by montmorillonite of nitrification in soil - Kunc, F; Stotzky, G (Folia microbiologica, 1980)
A soil naturally containing montmorillonite (M) was amended with 10% M and sequentially perfused with glyeme, with fresh glyeme being added every 16--17d after nitrification of the previously added glycine-nitrogen had reached a plateau. In some systems, the old perfusates were replaced each time with a fresh glycine solution; in others, the initial perfusate was not replaced but only adjusted each time to the original 200 ml volume and a comparable glycine concentration (140 micrograms NH2-N/ml). The incorporation of M enhanced the rates of heterotrophic degradation of glycine and subsequent autotrophic nitrification, but these stimulatory effects decreased with each successive perfusion. The reasons for these decreases are not known, but they did not appear to be related to inorganic nutrition, as perfusion with a mixed cation solution after five perfusion cycles did not significantly enhance nitrification in either the check or M-amended soils during three subsequent perfusions with glycine. The enhancement of nitrification by M appeared to be a result, in part, of the greater buffering capacity of the M-amended soil, as indicated by lesser reductions in the pH of perfusates from the M-amended soil, by titration curves of the soils, and by the greater and longer stimulation of nitrification in the check soil amended with 1% CaCO3, which had a greater buffering capacity than did M. The stimulation by CaCO3 may also have been partially the result of providing CO2 for the autotrophic nitrifyers. Significant concentrations of nitrite accumulated only in perfusates from soil amended with CaCO3. Air-drying and remoistening the soils enhanced nitrification of subsequently added glycine, especially in the check soil. The importance of pH-mediation, of the production of inhibitors, and/or of feed-back inhibition was indicated by the lower rate and extent of nitrification in systems wherein the perfusates were not replaced between successive additions of glycine. Although the results of these studies confirmed previous observations that M enhances the rate of nitrification in soil, the mechanisms responsible for this stimulation are still not known.
Keywords: dusitany; bentonit; glycin; půdní mikrobiologie; chemická stimulace; Biodegradation, Environmental; Glycine; Nitrates; dusičnany; biodegradace; Nitrobacter; Soil Microbiology; kvartérní amoniové sloučeniny; Bentonite; Stimulation, Chemical; Nitrites; Quaternary Ammonium Compounds